Analisis Informasi Citra Anatomi antara Teknik Breath-Hold dan Trigger pada Pemeriksaan Magnetic Resonance Cholangiopancreatography (MRCP) Menggunakan Sequence T2 Half Fourier Acquisition Single Shot TSE (HASTE) Coronal Slab - Yusron Adi Utomo; Bambang Satoto; Rini Indrati (Jurnal Imejing Diagnostik (JImeD), 2016)
Background: There are two image acquisition techniques in MRCP examination, which are breath-hold and trigger technique. Acquisition process in breath hold occurs when the patient holds their breath, meanwhile trigger technique uses respiratory gatting that functioned to monitor patient’s respiration and the acquisition occurs in the transition phase of inspiration and expiration. In Royal Taruma Jakarta Hospital this two technique are used sustainably, but in other hospital, such as Hasan Sadikin Bandung Hospital just uses one technique. This research aims to know the difference of anatomic image information of breath-hold and trigger technique in MRCP examination using T2 HASTE sequence coronal slab and to know which examination technique is better to produce anatomic image information between breath-hold and trigger technique.Methods: This research type was quantitative research with the observational approach. The data obtained by scanning 10 patients using breath-hold and trigger technique in Royal Taruma Jakarta Hospital. The image result was scored by radiology physician using checklist. The obtained data was analyzed with Wilcoxon test to know the difference of anatomic image information and which technique is better to produce anatomic image information between breath-hold and trigger technique.Results: The result showed that there were differences of anatomic image information of breath-hold and trigger technique on MRCP examination using T2 HASTE sequence coronal slab with p-value 0,011. Trigger technique produced better anatomic image information than breath-hold technique.Conclusion: There were differences of anatomic image information of breath hold and trigger technique on MRCP examination using T2 HASTE sequence coronal slab. Trigger technique produced better anatomic image information than breath-hold technique